Eosinophils in COPD: how many swallows make a summer?. Issue 1 (25th January 2018) - Hamad, Ghassan Ahmed; Cheung, Wesley; Crooks, Michael G.; Morice, Alyn H.
There is considerable controversy over the place of the blood eosinophil as a biomarker in chronic obstructive pulmonary disease (COPD). Recent literature suggests its use in assessing responsiveness to inhaled corticosteroids (ICS) [1, 2] and in predicting exacerbations [3, 4]. Other studies either wholly or partially refute these associations [5–7]. We suggest that what underlies this confusion is the failure to understand the temporal variation in the biomarker, and the inherent imprecision in the collection of associated end-point data. Repeated measures of eosinophil counts increased the proportion of eosinophilic patients http://ow.ly/LhnV30hlR5j